RAISING THE LEGAL AWARENESS AND LEGAL CULTURE THE REQUIREMENT OF THE TIME (American Journal of Interdisciplinary Research and Development, 2022)
This article highlights the role of legal awareness and legal culture in building a law - governed state and, above all, improving the legal literacy of rach person’s legal immunity